An investigation of the relationship between physical fitness, self-concept, and sexual functioning - Lia M Jiannine (Wolters Kluwer Medknow Publications, 2018)
Background: Obesity and inactivity have led to an increasing number of individuals with sexual dysfunctions (43% of women; 31% of men). Small bouts of exercise can drastically improve sexual functioning. Thus, the present study is designed to examine the effects of physical fitness and self-concept on sexual functioning. Materials and Methods: Fitness assessments and questionnaires were administered to 133 participants between the ages of 18 and 50 years. Physical fitness was assessed through body composition, cardiovascular endurance, muscular strength, and muscular endurance. Self-concept was presented as a total self-concept score and as six individual concepts of self. Sexual function was presented as both an aggregate score and five separate constructs of sexual functioning - fantasy/cognition, arousal, orgasm, behavior/experience, and drive/desire. Results: The results indicated that sexual behavior/experience was predicted by body fat percentage. In men, fantasy was related to total self-concept; sexual behavior/experience was related to likeability. In women, arousal was predicted by cardiovascular endurance. Total self-concept was related to both orgasm and sex drive/desire. Power and muscular strength were significantly related to number of sexual partners in women but not men. Conclusions: The present study adds to the growing body of evidence indicating a positive relationship between physical fitness and sexual health. Individuals with sexual dysfunctions, particularly women, who are not persuaded by the currently publicized benefits of physical activity, may be inclined to exercise to improve sexual functioning.